Application of Differentiated Learning to Increase Participation and Learning Outcomes of Class VII Rafflesia Students at SMP Negeri 4 Palu - Septiana, Ayu; Taslia, Taslia; Amus, Sunarto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The aim of this research is to increase the participation and learning outcomes of class VII Reflesia students at SMPN 4 Palu through the application of differentiated learning in Civics subjects. This research is class action research (Class Action Research) which consists of two cycles. Each cycle consists of action planning, action implementation, evaluation (observation) and reflection. The research subjects were class VII Reflesia students at SMPN 4 Palu, totaling 32 students consisting of 15 male students and 17 female students. Data sources come from teachers and students obtained through observation, interviews, tests and document review. The data analysis technique used is descriptive analysis. The results of the research show that: (1) The application of differentiated learning has a significant effect on student participation in PPKn learning in class VII Reflesia in cycle I, student participation had an average of 74.48% (Quite Good) whereas during the implementation of cycle II The average student participation score increased to 93.61% (Very Good), this shows an increase in the average student participation score of 19.13%. (2) There was an increase in student learning outcomes in Civics learning by implementing differentiated learning in class VII Reflesia SMP Negeri 4 Palu, where student learning outcomes in cycle I showed an average value of student learning outcomes of 69.87%, experiencing an increase in implementation. cycle II where the average value of student learning outcomes was 81.12%, this shows an increase of 11.25%.